Optimizing the Dose of Cow Manure and Pruning on Sweet Corn (Zea mays saccharata Sturt.) Growth and Production - Muhammad Nurdin Hidayat; Sutinisutini; Ramdhan Hidayat (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Sweet corn (Zea mays saccharata Sturt.) has high economic value; however, its productivity in Indonesia remainslow, leading to partial reliance on imports to meet demand. This study aimed to determine the optimal dose ofcow manure and pruning method to enhance the growth and yield of sweet corn. The research was conducted inBalongpanggang, Gresik, East Java, from October 2024 to January 2025, using a factorial Completely RandomizedDesign (CRD) with three replications. The first factor was the dose of cow manure (10, 20, and 30 tons/ha), andthe second factor was pruning type (no pruning, pruning three leaves below the cob, pruning male flowers, andpruning both leaves and male flowers). Data were analyzed using ANOVA followed by a 5% BNJ test. The resultsindicated that the combination of 30 tons/ha of manure with pruning three leaves below the cob and male flowersproduced the best outcomes in vegetative growth parameters, including plant height, number of leaves, stemdiameter, cob weight, cob diameter, and sweetness content. These findings confirm that integrating organicfertilization with targeted pruning is an effective strategy for sustainably increasing sweet corn productivity.